Hysteroscopic removal of retained products of conception withenhanced vascularity: a study of reliability - G. Garuti; E. Castellacci; S. Calabrese; S. Calzolari (IMR Press, 2020)
Purpose of Investigation: Retained products of conception (RPOC) is the leading cause of postpartum or post-abortion hemorrhage. RPOC showing high vascularity at ultrasound assessment (HV-RPOC) showed an enhanced hemorrhagic risk following blind surgical uterine emptying. The authors describe the clinical outcome of patients suffering from HV-RPOC undergoing hysteroscopic removal. Material and Methods: Cohort of symptomatic patients suffering from HV-RPOC following miscarriages, pregnancy terminations, and term deliveries. After ultrasound selection based on color-Doppler showing HV-RPOC, all patients underwent hysteroscopic resection. Results: Twenty-seven patients met the selection criteria. HV-RPOC were found in 14 and six women after first and second trimester pregnancy termination, respectively. In seven women RPOC were found after term delivery. In 18 women (66.6%) RPOC were found firmly adherent to myometrium. Neither intra- nor postoperative complications were recorded. Hysteroscopy follow-up was carried-out in 16 patients. Normal findings were found in 15 women, in one case a mild adhesion was observed. Conclusion: HV-RPOC are often characterized by abnormally adherent placenta, suggesting that an accreta can be an underlying etiology. A reliable management can be accomplished by hysteroscopic resection.